Continuation of enteral nutrition in the haemodynamically unstable burns patient on high dose intravenous vasopressor support: a five year retrospective study - Rooi, Adelaide Lilian (My University, 2017)
Introduction Early enteral nutrition and the continuation of enteral nutrition are critical factors in burn patients, who typically have higher nutritional needs due to their post-injury hypercatabolic state and their additional need for nutrients to aid in the healing of wounds and skin grafts. In the critically ill patient, enteral nutrition is the preferred mode of administration. However, disagreement exists regarding the simultaneous use of enteral nutrition and intravenous vasopressor agents in the haemodynamically unstable patient-which is the current protocol at the Chris Hani Baragwanath Academic Hospital. [Abbreviated Abstract. Open document to view full version]
Keywords: Enteral Nutrition